Increasing milking frequency in fresh cows: milk characteristics and reproductive performance - Jeffrey S. Stevenson; John E. Shirley (Kansas Agricultural Experiment Station Research Reports, 2003)
Increased milking frequency during partial or whole lactations increases milk yields, but generally reduces percentages of milk fat and protein. Because of greater milk volume, total fat and protein are not reduced. Combining bovine somatotropin (bST) with increased milking frequency is additive. In other words, milk increases in response to both factors. In some studies, increased milking frequency during early lactation improves udder health, as evidenced by reduced somatic cell scores. Reproductive efficiency generally declines when examined on whole herd basis. When examined in single herds with or without bST, pregnancy rates may not be reduced because of increased milking frequency, and in some cases may be improved.; Dairy Day, 2003, Kansas State University, Manhattan, KS, 2003;
Keywords: Dairy Day; 2003; Kansas Agricultural Experiment Station contribution; no. 04-129-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 919; Dairy; Milking frequency; Milk yields; Reproductive performance